Implementasi Pembelajaran Berbasis Masalah untuk Mengembangkan Kompetensi Abad 21 dalam Mata Pelajaran Matematika - Nurholipah .; Rina Diana lestari; Hikmah Mas'udah; Rudy Adriyadi (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aimed to analyze the implementation of Problem-Based Learning (PBL) in mathematics and its effect on developing 21st-century competencies among students. A mixed-method approach, combining quantitative and qualitative designs, was employed. The quantitative approach used a one-group pretest-posttest quasi-experimental design to measure changes in students’ 4C competencies (critical thinking, creativity, collaboration, communication), while the qualitative approach explored the learning process, student interactions, motivation, attitudes, and teacher experiences. Data were collected through pretests and posttests, observations, semi-structured interviews, and documentation of lesson plans and student worksheets. The findings revealed that PBL significantly enhanced students’ 21st-century competencies, with an average score of 86.6%. Student learning activities increased across group discussions, contextual problem-solving, critical thinking, creativity, collaboration, and communication. Motivation and positive attitudes, including responsibility, discipline, and honesty, also improved. PBL enables students to explore mathematical concepts through real-life problems, think creatively, collaborate in groups, and communicate solutions effectively. Challenges included time constraints and variations in students’ abilities, which required differentiation and time management strategies. The study confirmed that PBL was an effective strategy to integrate cognitive, affective, and social aspects while preparing students for 21st-century challenges. Implications for teachers included enhancing their ability to design contextual problems, facilitate discussions, and utilize digital media effectively. The study demonstrated that PBL not only strengthened students’ mathematical understanding but also fostered higher-order thinking skills, collaborative behaviors, and reflective attitudes, contributing to the development of competent, adaptive, and innovative learners.